Emerging therapeutics and relevant targets for chronic Hepatitis B - Song, Il Han (Turkish Journal of Gastroenterology, 2016)
Abstract Chronic hepatitis B virus (HBV) infection is a global health problem for the pursuit of complete virus eradication and immunity acquisition to prevent liver disease progression. Currently, interferon-alpha, with the underlying mechanism of host immunomodulation, and nucleos(t)ide analogs, with the underlying mechanism of inhibition of viral replication, are used for the treatment of patients with chronic hepatitis B. Despite remarkable improvement in the virological, serological, biochemical, and histological response to current therapeutics, we are still far from meeting the therapeutic goals, e.g., clearance of HBV DNA/covalently closed circular DNA (cccDNA) in the serum/liver tissue and seroconversion of hepatitis B surface antigen (HBsAg) to anti-HBs in the present antiviral era. Recently, HBV replication cycle-related, viral RNA interference-based, and host immune-mediated therapeutic targets and relevant anti-HBV agents have been newly introduced and investigated in the preclinical and clinical fields. This review discusses emerging therapeutics and relevant targets in the management of chronic hepatitis B.